Kif21B mediates the effect of estradiol on the morphological plasticity of mouse hippocampal neurons - Ganchala, Danny; Pinto-Benito, Daniel; Baides, Elisa; Ruiz-Palmero, Isabel; Grassi, Daniela; Arevalo, Maria Angeles (Frontiers in Molecular Neuroscience, 2023)
Introduction Neurons are polarized cells, and their ability to change their morphology has a functional implication in the development and plasticity of the nervous system in order to establish new connections. Extracellular factors strongly influence neuronal shape and connectivity. For instance, the developmental actions of estradiol on hippocampal neurons are well characterized, and we have demonstrated in previous studies that Ngn3 mediates these actions. On the other hand, Kif21B regulates microtubule dynamics and carries out retrograde transport of the TrkB/brain-derived neurotrophic factor (BDNF) complex, essential for neuronal development. Methods In the present study, we assessed the involvement of kinesin Kif21B in the estradiol-dependent signaling mechanisms to regulate neuritogenesis through cultured mouse hippocampal neurons. Results We show that estradiol treatment increases BDNF expression, and estradiol and BDNF modify neuron morphology through TrkB signaling. Treatment with K252a, a TrkB inhibitor, decreases dendrite branching without affecting axonal length, whereas. Combined with estradiol or BDNF, it blocks their effects on axons but not dendrites. Notably, the downregulation of Kif21B abolishes the actions of estradiol and BDNF in both the axon and dendrites. In addition, Kif21B silencing also decreases Ngn3 expression, and downregulation of Ngn3 blocks the effect of BDNF on neuron morphology. Discussion These results suggest that Kif21B is required for the effects of estradiol and BDNF on neuronal morphology, but phosphorylation-mediated activation of TrkB is essential only for axonal growth. Our results show that the Estradiol/BDNF/TrkB/Kif21B/Ngn3 is a new and essential pathway mediating hippocampal neuron development.